UAV survey of a coastal cliff face – Selection of the best imaging angle. (June 2019) - Jaud, Marion; Letortu, Pauline; Théry, Claire; Grandjean, Philippe; Costa, Stéphane; Maquaire, Olivier; Davidson, Robert; Le Dantec, Nicolas
Highlights: Impact of the UAV camera tilting angle on the 3D cliff face reconstruction. Because of occlusions, irrelevance of nadir pointing camera for sub-vertical cliffs. Satisfying accuracy and texture for both 20°, 30° and 40° off-nadir imaging angles. Other parameters impacting tiepoint detection in the reconstruction process. Abstract: UAVs are relevant for monitoring cliff faces. In this study, several flights are performed with various imaging angles (nadir, 20°, 30° and 40° off-nadir) to assess the impact of the imaging angle on the 3D cliff face reconstruction. Occlusions issues arising with sub-vertical cliffs make nadir surveys nearly irrelevant. The results obtained with 20°, 30° and 40° off-nadir imaging angles are satisfactory regarding texture restitution and accuracy with respectively 5.5 cm, 5.9 cm and 4.9 cm of error, higher tilting angles yielding better reconstructions on sub-vertical or overhanging parts of the cliff. This article also investigates other parameters affecting tiepoint detection on the cliff face, as the effective overlap, the UAV-cliff face distance and the cliff face illumination. Guidelines are provided for UAV survey parameterization, aiming at capturing the whole cliff face with a good trade-off between distance to the cliff, flight height and spatial resolution of the photographs.